Non‐paraneoplastic autoimmune subepidermal bullous disease associated with fatal bronchiolitis obliterans. Issue 4 (3rd December 2016) - Orime, Mari; Tomiyama, Katsuhiro; Hashidate, Hideki; Yoshida, Satoru; Hokari, Satoshi; Tsuda, Akiko; Yokoyama, Hisashi; Narita, Jun‐ichi; Uchida, Youhei; Kanekura, Takuro; Abe, Riichiro; Ishii, Norito; et al.
Abstract: Bronchiolitis obliterans is a small‐airway obstructive lung disease for which immunologically mediated pathogenesis is supposed. Frequent association of bronchiolitis obliterans with paraneoplastic pemphigus is well known, but its association with other autoimmune bullous diseases has not been reported except for a case of anti‐laminin‐332‐type mucous membrane pemphigoid in a patient with chronic graft‐versus‐host disease. We report a case of non‐paraneoplastic autoimmune subepidermal bullous disease associated with fatal bronchiolitis obliterans in a patient without transplantation. Although the patient's serum contained immunoglobulin (Ig)A antibodies to the 180‐kDa bullous pemphigoid antigen/type XVII collagen and IgG antibodies to laminin‐332, diagnosis of either linear IgA bullous dermatosis or mucous membrane pemphigoid could not be made because of the failure to detect linear IgA deposition at the basement membrane zone by direct immunofluorescence and the lack of mucous membrane lesions. Physicians should be aware that autoimmune bullous diseases other than paraneoplastic pemphigus can also associate with this rare but potentially fatal lung disease.